H1N1 Influenza Virus-Infected Nasal Mucosal Epithelial Progenitor Cells Promote Dendritic Cell Recruitment and Maturation - Zhu, Fangyuan; Teng, Zhenxiao; Zhou, Xuanchen; Xu, Runtong; Bing, Xin; Shi, Lei; Guo, Na; Wang, Min; Liu, Chengcheng; Xia, Ming (Frontiers in Immunology, 2022)
The barrier function of nasal mucosa epithelial cells plays an irreplaceable role in the spread and expansion of viruses in the body. This study found that influenza A virus H1N1 can induce apoptosis of nasal mucosal epithelial progenitor cells, cause an inflammatory response, and trigger the maturation and recruitment of nasal submucosal dendritic cells (DCs), but the mechanism remains unclear. Therefore, we used RNA-seq and high-resolution untargeted metabolomics to sequence and perform combined bioinformatic analysis of H1N1-infected nasal mucosal epithelial cells from 6 different patients. The abnormal arginine metabolism signaling pathway caused by H1N1 virus infection was screened out, and arginase inhibitors were used to interfere with the abnormal arginine metabolism and the maturation and recruitment of submucosal DCs caused by the H1N1 virus in vitro and in vivo. We conclude that H1N1 influenza virus promotes the recruitment and maturation of submucosal DCs by causing abnormal arginine metabolism in nasal mucosal epithelial cells, thereby triggering respiratory mucosal immunity.